Analytical and experimental determination of the failure-critical pressure of pipe structures manufactured by PBF-LB/M - Koers, Thorsten; Magyar, Balázs; Bödger, Christian; Tröster, Thomas (International Journal of Pressure Vessels and Piping)
The state of the art shows that PBF-LB/M offers great potential for pressure-loaded parts, with significant weight reductions and simultaneous optimization of flow resistance. This study is aimed at applying existing calculation methods for pressure-loaded parts to additively manufactured pipe structures, considering the two materials EN AC-43000 (3.2381, AlSi10Mg) and AISI 316L (1.4404, X2CrNiMo17-12-2). For this purpose, systematic tensile tests are carried out for both materials. In addition, a statistical evaluation is performed to determine the design-relevant strength characteristics with a survival probability Ps of 97.5 % for both materials in the as-built and heat-treated condition. Pipe specimens are manufactured, half of which are heat treated, geometrically measured and then subjected to a burst pressure test to experimentally determine the failure-critical internal pressure. These results are compared with calculated burst pressures. The calculations are based on the application-relevant methods identified in this study, considering the strength values determined for the respective material condition. This comparison is used to assess the suitability of the calculation methods for additively manufactured pipe structures, based on the materials investigated.
Keywords: PBF-LB/M; Pipe structures; Strength assessment; Burst pressure test; Geometrical deviations